The influence disclosure enterprise risk management and intellectual capital to firm value through disclosure of sustainability report as variables intervening - Putri, Agnes Karunia Samesta; Karsam, Karsam; Solihin, Solihin; Kusumawardhani, Devi (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2024)
The purpose of this study is to examine the effect of enterprise risk management disclosure and intellectual capital on firm value through sustainability report disclosure as an intervening variable. This research method is quantitative, with a sample size 16 companies listed on the Indonesia Stock Exchange in the LQ 45 index during the period 2019-2023. The data processing used in this study involves Smart PLS data analysis software. The results of direct tests show that enterprise risk management disclosure affect firm value, intellectual capital has no effect on firm value, and sustainability report disclosure affect firm value. Additionally, enterprise risk management disclosure affect sustainability report disclosure, while intellectual capital has no effect on sustainability report disclosure. The results of indirect tests indicate that enterprise risk management and intellectual capital disclosure affect sustainability report disclosure, but they do not affect firm value through sustainability report disclosure, meaning that the company's sustainability report disclosure is not an intervening variable for companies listed on the Indonesia Stock Exchange in the LQ45 index.